Reliability of resting metabolic rate between and within day measurements using the Vyntus CPX system and comparison against predictive formulas. Issue 1 (March 2023) - Iraki, J.; Paulsen, G.; Garthe, I.; Slater, G.; Areta, J.L.
Background: To detect longitudinal changes of resting metabolic rate (RMR) resulting from the effects of energetic stress, reliable RMR measurements are crucial. The Vyntus CPX is a new automated indirect calorimetry system for which RMR reliability has not been determined. Additionally, its agreement with common predictive RMR formulas is unknown.Aim: To determine the within and between-day reliability of RMR measurements using the Vyntus CPX system and its agreement with predictive RMR formulas.Methods: Young (31 ± 7 years) healthy participants (n = 26, 12 females, 14 males) completed three measurements of RMR, two consecutive measures on the same day, one the day before/after, all under standardised conditions. Reliability was assessed with pairwise comparisons of between-day at the same time (BDST), within day consecutive measurements (WDCM) and between-day different time (BDDT), for parameters of reliability (mean change (MC), intraclass correlation (ICC) and typical error of measurement (TEM)). Measured RMR values (kcal/day) were compared against predictive values of 4 common formulas.Results: Parameters of reliability (mean, (95% confidence interval)) were: -BDST: MC, 0.2(-2.3—2.7)% (p = 0.67); ICC, 0.92(0.84—0.97); TEM, 4.5(3.5—6.2)%. -WDCM: MC, −2.5(-6.2—1.3)% (p = 0.21); ICC, 0.88(0.74—0.88); TEM, 7.0(5.4—9.8)%. -BDDT: MC, −1.5(-4.8—1.9)% (p = 0.57); ICC, 0.90(0.76—0.95); TEM, 6.1(4.8—8.5)%. RMRratios (measured/predicted) were: 1.04 ± 0.14 (Nelson, p = 0.13), 1.03 ± 0.10 (Mifflin, p = 0.21), 0.98 ± 0.09 (Harris-benedict, p = 0.30), 0.95 ± 0.11 (Cunningham1980, p = 0.01), 1.00 ± 0.12 (Cunningham1991, p = 0.90) and 0.96 ± 0.13 (DXA, p = 0.03).Conclusions: The Vyntus CPX is reliable and measured RMR values agreed with four predictive formulas but are lower than Cunningham1980 and DXA RMR estimates for this population.